Humayunama : Gulbadan's Account : Simplified and Abridged - Dossal, Zubeida A. (Karachi Oxford University Press, 2001)
The Historical Readers series is a supplementary text for secondary and upper secondary classes which aims to develop students interest in the history of the region. Drawing from authentic Mughal sources, the diaries and accounts of personal as well as court life, maintained by the rulers, their children, and court officials, give readers a fascinating glimpse into the life and times of a dynasty that ruled the subcontinent for over 300 years. Abridged and simpli?ed, the books have been attractively illustrated in a style that matches their mood and content. Student's Books
Includes Colored Illustrations
Keywords: Humayun, -- Emperor of Hindustan, -- 1508-1556